WeChat-platform-based education and care program as a candidate approach to relieve anxiety, depression, and post-traumatic stress disorder in parents of pediatric and adolescent patients with osteosarcoma - Wu, Jing; Meng, Jie; Li, Honghe (Frontiers in Psychology, 2022)
Background WeChat is the main social platform in China, characterized by its versatility and ease of communication. This study aimed to explore the effect of a WeChat-platform-based education and care (WBEC) program on relieving anxiety, depression, and post-traumatic stress disorder (PTSD) in parents of pediatric and adolescent patients with osteosarcoma. Methods In total, 48 patients and 86 parents were enrolled in this randomized, controlled study and then assigned to the WBEC program (24 patients and 45 parents) and the usual education and care (UEC) program (22 patients and 41 parents) for 6 months as a 1:1 ratio. Results Parents in the WBEC group had lower Hospital Anxiety and Depression Scale (HADS) for anxiety (HADS-A) scores at M3 (7.8 ± 2.2 vs. 9.1 ± 2.5; p = 0.010) and M6 (7.7 ± 2.5 vs. 8.9 ± 2.4; p = 0.027) when compared to the UEC group, while anxiety rate was only decreased at M3 (43.2% vs. 63.4%; p = 0.049) in the WBEC group. Meanwhile, parental HADS for depression (HADS-D) scores were reduced at M3 (7.0 ± 2.0 vs. 8.0 ± 2.1; p = 0.047) and M6 (7.1 ± 1.9 vs. 8.0 ± 2.4; p = 0.045) in the WBEC group when compared with the UEC group; while depression rate remained the same. Parental Impact of Event Scale-Revised (IES-R) scores were slightly reduced among the WBEC group at M6 when compared with the UEC group [12.0 (interquartile range (IQR): 10.0–20.8] vs. 15.0 (IQR: 9.5–25.0; p = 0.077)], but not statistically significant. Conclusion WeChat-platform-based education and care is considered a feasible intervention to reduce anxiety and depression in parents of pediatric and adolescent patients with osteosarcoma, while also providing mild relief from PTSD.